Effectiveness and suitability of vapor heat treatment in disinfestation of export mango fruit, cultivar Abu Samaka, from fruit flies - Mohamed, Ahmed H.; Kamal, Islam; Abdel Rauof, Fatima; Hussein, Dawoud; Babiker, Salah; Elsheikh, Badreldin; El Badri, Gamal; Mohamed, Abdel Rahman (Gezira Journal of Agricultural Science, 2017)
Sudan has a great potential for the export of mango ( Mangifera Indica L.) but fruit flies, mainly Bactrocera dorsalis (Hendel) , Ceratitis cosyra (Walker), C. capitata (Wiedmann) and B. zonata (Saunders) are threatening the export industry. The countries importing mango require disinfestation treatment against fruit flies as a quarantine regulation. Effectiveness and suitability of vapor heat treatment (VHT) for disinfestation of the Sudanase mango cultivar Abu Samaka were undertaken in this study. In the VHT, the relative humidity of the treatment chamber was maintained at 99.7% and the temperature of the fruit pulp was raised gradually to reach 46.7°C in 5 hours then kept at this degree for 30 minutes before hydro-cooling for 20 minutes. For evaluation of the effectiveness of the treatment, naturally and artificially infested fruits were examined for fruit flies after treatment and compared with their respective untreated samples. To assess suitability of the treatment with respect to quality of the mango fruit, respiration rate, peel color, weight loss, flesh firmness, ascorbic acid content, total soluble solids, titratable acidity and reducing sugars were measured in the treated and control fruits.  The VHT was found effective in disinfestation of the mango cultivar Abu Samka from fruit flies and did not adversely affect the fruit market quality and increased the shelf life.